Parent–Child Neural Dynamics During a Stressful Task: Probing Associations With Temperament and Anxiety - Joscelin Rocha-Hidalgo; Harmony Nguyen; Dakota Reis; Denny Schaedig; Kahlil I. Thompson; Susan B. Perlman; Koraly E. Pérez-Edgar (Clinical Psychological Science, 2026)
Dynamic social interactions between parents and children can contribute to anxiety risk, amplifying shared genetic risk. Research has focused on observed behaviors to explain intergenerational transmission. Neural synchrony may contribute as a biological conduit for behavioral transmission of risk. We examined 109 parent–child dyads (age: M = 5.81 years, SD = 1.2; 55 girls; 66 mothers) during a mildly stressful interaction (Disruptive Behavior Diagnostic Observation Schedule: Biological Synchrony) using functional near-infrared spectroscopy. Synchrony was lower during the recovery block than during baseline, and there were no significant differences between the stressful and baseline conditions. Synchrony significantly decreased in dyads with children higher in effortful control during recovery, consistent with flexible adjustment after stress. Dyads with children higher in fear showed reduced ventrolateral prefrontal cortex synchrony during recovery compared with baseline. Higher parental state anxiety was associated with lower ventrolateral prefrontal cortex synchrony. Neural synchrony may be sensitive to context and individual traits linked to anxiety risk and resilience, providing potential targets for prediction and intervention.